Future of the firm - Bersin, Josh, 1956- (O'Reilly Media, 2019)
Today's successful businesses are increasingly digital and technologically astute, but how do they attract and manage employees in a world where two billion people work part-time? How do they develop a workforce when automation is advancing? And how do they serve customers and attract and retain employees when competition for both is high and trust is at an all-time low? In this O'Reilly Radar report, Josh Bersin, Tim O'Reilly, Roger Magoulas, and Mike Loukides address what business leaders, tech leaders, and decision makers can expect, how they can prepare, and what they should learn to shape the future of the business. These lessons affect much more than the bottom line. This report covers big-picture trends we expect to impact the future success of all firms, including: Trust in business is changing: customers seek firms whose values reflect their own. Employees want satisfaction and meaning, not just money and security. The shift to AI and machine learning is changing almost every job. Companies are becoming networked marketplaces that build on core competencies while outsourcing the rest. Many firms offer compensation beyond pay, including alternate work relationships, flexible workplaces, and training opportunities. Embracing diversity requires solving compensation problems, creating a safe workplace, and valuing an employee's opinions.